Innovation in public service delivery: essays on the social impact bond - Economy, C (2021)
Following the requirements of an article-based dissertation, this thesis offers three separate articles that explore the effect of the social impact bond (SIB) model on processes of public service delivery. SIBs are an outcomes-based approach to funding social services, where typically a private investor gives upfront capital to a service delivery organization and is then paid back by the government based on the achievement of outcomes. Despite over ten years of experimentation, there is a critical gap in our understanding of how SIBs work in practice and the effects of the model on public service delivery. This thesis draws on theories of new public management, i.e. the incorporation of private sector mechanisms in public service delivery, to investigate various aspects of the ‘SIB effect’ related to financial incentives, performance targets, risk transfer, multi-sector collaboration, and provider flexibility.